2007
DOI: 10.1111/j.1532-5415.2007.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Hypertension Prevalence, Awareness, Treatment, and Control in Older U.S. Adults: Data from the National Health and Nutrition Examination Survey 1988 to 2004

Abstract: There was a significant increase in hypertension prevalence from 1988 to 2004. Hypertension control continues to be problematic for women, persons aged 70 and older, non-Hispanic blacks and Mexican Americans, and individuals with diabetes mellitus and CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
209
9
12

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(257 citation statements)
references
References 27 publications
27
209
9
12
Order By: Relevance
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…17 In particular, the lack of improvement in SBP may prevent the patients to receive the benefits of otherwise improved hypertension care. Compared with the prevalences of hypertension in our study, those reported since 2000 in other studies by age and sex have been lower in most, [18][19][20][21][22][23][24][25][26][27] but not in all populations. 27,28 As in our paper, the rate of awareness of hypertension in these reports was usually more than 60%.…”
Section: Discussioncontrasting
confidence: 91%
“…20,23 The hypertension care showed an improvement during 2003-2006 also in the Health Survey for England in 2006, particularly in women. 26 In the National Health and Nutrition Examination Survey during 1988-2004, hypertension prevalence increased significantly in all US older adults aged 60 years or over, 19 by race/ethnicity in both non-Hispanic white and black people. 27 In older men hypertension awareness, treatment and control increased significantly and the rates reached those seen in women.…”
Section: Discussionmentioning
confidence: 99%
“…у больных сахарным диабетом), как и доля участников, отве-тивших на терапию, была выше при приеме олме-сартана. Эти данные имеют важное клиническое значение, поскольку, согласно результатам популя-ционных исследований, эффективность контроля артериального давления у получающих антигипер-тензивную монотерапию пожилых больных не пре-вышает 30-40% [11,12]. В нашем исследовании контроль давления был достигнут чаще, чем у каж-дого второго пациента (59%).…”
Section: Discussionunclassified
“…Согласно результатам рандомизированных исследований, выполненных у лиц с эссенциальной артериальной гипертензией в возрасте 65 лет и стар-ше, антигипертензивная терапия приводит к выра-женному снижению сердечно-сосудистой заболевае-мости и смертности [2][3][4][5][6][7][8][9][10]. В то же время, как пока-зал целый ряд эпидемиологических исследований [11][12][13][14], охват антигипертензивной терапией и конт-роль артериального давления у пациентов с гипер-тензией остается неадекватным, в особенности у пожилых больных.У большинства пожилых пациентов имеет место сочетание нескольких факторов сердечно-сосудисто-го риска, поражения органов-мишеней и ассоцииро-ванных клинических состояний. Следо вательно, у этой категории больных антигипертензивная тера-пия должна быть не только эффективной, но и хоро-шо переносимой [15].…”
unclassified
“…4,6 Recognizing the elderly as an at-risk population, studies in various countries have documented the prevalence and correlates of hypertension and of awareness, treatment and control of hypertension among the elderly. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] These studies suggest considerable heterogeneity for the prevalence of these conditions across elderly subgroups, defined by socio-demographic or health characteristics. Furthermore, neither the prevalence nor the identified correlates are uniform across countries.…”
Section: Introductionmentioning
confidence: 99%